IMPLEMENTATION OF ACCOUNTING IN MSMEs (JURNAL ECONOMICA : Research of Economic And Economic Education, 2018)
This study aims to analyze: 1) the influence of the level of education on the application of accounting in the preparation of financial statements. 2) the influence of the length of business on the application of accounting in the preparation of financial statements. 3) the influence of the business scale on the application of accounting in the preparation of financial statements. 4) the influence of accounting training on the application of accounting in the preparation of financial statements. Based on the data obtained in Lubuk Begalung Subdistrict, the results of the study showed: 1) The level of education had a significant effect on the application of accounting in the preparation of financial statements. 2) Length of business has a negative and insignificant effect on the application of accounting in the preparation of financial statements. 3) Business scale has a significant effect on the application of accounting in the preparation of financial statements. 4) Accounting training has a significant effect on the application of accounting in the preparation of financial statements.